How to Study the Metabolism of New Psychoactive Substances for the Purpose of Toxicological Screenings—A Follow-Up Study Comparing Pooled Human Liver S9, HepaRG Cells, and Zebrafish Larvae - Wagmann, Lea; Frankenfeld, Fabian; Park, Yu Mi; Herrmann, Jennifer; Fischmann, Svenja; Westphal, Folker; Müller, Rolf; Flockerzi, Veit; Meyer, Markus R. (Frontiers in Chemistry, 2020)
The new psychoactive substances (NPS) market continues to be very dynamic. A large number of compounds belonging to diverse chemical groups are still appearing. This makes their detection in biological samples challenging for clinical and forensic toxicologists. Knowledge of the metabolic fate of NPS is crucial for developing comprehensive screening procedures. As human studies are not feasible due to ethical concerns, the current study aimed to compare the NPS’ metabolic pattern in incubations with pooled human liver S9 fraction (pHLS9), human liver HepaRG cells, and zebrafish larvae. The latter model was recently shown to be a promising preclinical surrogate for human hepatic metabolism of a synthetic cannabinoid. However, studies concerning other NPS classes are still missing and therefore an amphetamine-based N-methoxybenzyl (NBOMe) compound, a synthetic cathinone, a pyrrolidinophenone analog, a lysergamide, as well as another synthetic cannabinoid were included in the current study. Liquid chromatography coupled to orbitrap-based high-resolution tandem mass spectrometry was used to analyze metabolic data. Zebrafish larvae were found to produce the highest number of phase I, but also phase II metabolites (79 metabolites in total), followed by HepaRG cells (66 metabolites). Incubations with pHLS9 produced the least metabolites (57 metabolites). Furthermore, the involvement of monooxygenases and esterases in the metabolic phase I transformations of 4F MDMB BINACA was elucidated using single enzyme incubations. Several cytochrome P450 (CYP) isozymes were shown to contribute, and CYP3A5 was involved in all CYP-catalyzed reactions, while amide and ester hydrolysis were catalyzed by the human carboxylesterase (hCES) isoforms hCES1b and/or hCES1c. Finally, metabolites were compared to those present in human biosamples if data were available. Overall, the metabolic patterns in HepaRG cells provided the worst overlap with that in human biosamples. Zebrafish larvae experiments agreed best with data found in human plasma and urine analysis. The current study underlines the potential of zebrafish larvae as a tool for elucidating the toxicokinetics of NPS in the future.